BP in Russia (B) - Bagley, Constance E., (SAGE knowledge. Cases., 2016)
In his tenure at BP, Robert Dudley had developed a reputation for coolness under fire. Which was a good thing, since his assignments frequently put him in the cross hairs of powerful and angry interests. Dudley, the son of a U.S. naval officer, grew up on the Gulf Coast of the United States and then moved with his family to the Chicago suburbs for his high school years. He studied chemical engineering at the University of Illinois and earned an MBA at Southern Methodist University in Dallas. Then he went to work for AMOCO, the Chicago-based oil giant, and became known for developing fields and doing deals in Texas, Scotland, Russia and China. Case study (B) follows on from case study (A).